-3(4x+3)+4(6x+1)=41

Simple and best practice solution for -3(4x+3)+4(6x+1)=41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4x+3)+4(6x+1)=41 equation:


Simplifying
-3(4x + 3) + 4(6x + 1) = 41

Reorder the terms:
-3(3 + 4x) + 4(6x + 1) = 41
(3 * -3 + 4x * -3) + 4(6x + 1) = 41
(-9 + -12x) + 4(6x + 1) = 41

Reorder the terms:
-9 + -12x + 4(1 + 6x) = 41
-9 + -12x + (1 * 4 + 6x * 4) = 41
-9 + -12x + (4 + 24x) = 41

Reorder the terms:
-9 + 4 + -12x + 24x = 41

Combine like terms: -9 + 4 = -5
-5 + -12x + 24x = 41

Combine like terms: -12x + 24x = 12x
-5 + 12x = 41

Solving
-5 + 12x = 41

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 12x = 41 + 5

Combine like terms: -5 + 5 = 0
0 + 12x = 41 + 5
12x = 41 + 5

Combine like terms: 41 + 5 = 46
12x = 46

Divide each side by '12'.
x = 3.833333333

Simplifying
x = 3.833333333

See similar equations:

| 2x+17=8(x-1)+1 | | y=0.5x+0.5 | | -17-2x=16-x | | (9a^-6b^2)/(17a^6b^-8) | | 1/3y+1/4=15/12-1/4 | | 3/4x7/12= | | 9x^2+4x-81=0 | | 3xsquared+11x=4 | | -4+.666y=.5y-5 | | 8/93/21 | | x=3x-127 | | 20=q | | 0.14y-1.6+3.12y+3.6= | | -6-3(2k-4)=18 | | a/3=-0.2 | | (9x+5)-(12x+7)= | | 3.4(2x+5)=-.2(2x+5) | | 12.3x=27.06 | | .5x+5=.33333333333333333333333333333333x+7 | | 4x^2(x-1)=0 | | 418=22x | | 1/4÷2/7= | | 28-4x/3=x | | 6-x=d | | 2x-44=-3 | | 12=8-f | | 4x+5y-6x-y= | | .07x+x=5 | | X+2.6=58.4 | | 12.25xy= | | X+0.75=12.25 | | f(n)=5n+4n |

Equations solver categories